Antihypertensive activity and vascular reactivity mechanisms of Vitex pubescens leaf extracts in spontaneously hypertensive rats - Ahmed Ahmed Al-Akwaa; Mohd Zaini Asmawi; Aidiahmad Dewa; Roziahanim Mahmud (Heliyon, 2020)
Background: Vitex pubescens has been used traditionally in hypertension treatment but not yet scientifically assessed. The objective of the study is to investigate the antihypertensive and vasorelaxant activities of V. pubescens, study its underlying pharmacological mechanisms, and identify the relevant vasoactive compounds. Methods: Successive extractions of V. pubescens leaf were carried out to produce petroleum ether (VPPE), chloroform (VPCE), methanol (VPME), and water (VPWE) extracts. Spontaneously hypertensive rats (SHRs) received a daily oral administration of the extracts (500 mg/kg/day; n = 6) or verapamil (15 mg/kg/day; n = 6) for 2 weeks, while the systolic and diastolic blood pressures were measured using non-invasive tail-cuff method. Vasorelaxation assays of the extracts were later conducted using phenylephrine (PE, 1 μM) pre-contracted aortic ring preparation. Mechanisms of vasorelaxation by the most potent fraction were studied using vasorelaxation assays with selected blockers/inhibitors. GC-MS was conducted to determine the active compounds. Results: VPPE elicited the most significant diminution in systolic and diastolic blood pressure of treated SHRs and produced the most significant vasorelaxation in the aortic rings. Vasorelaxant effects of F2-VPPE were significantly reduced in endothelium-denuded aortic rings by glibenclamide (1 μM), whereas calcium chloride and PE-induced contractions were significantly suppressed. Endothelium removal of the aortic rings or incubation with indomethacin (10 μM), atropine (1 μM), methylene blue (10 μM), propranolol (1μM) and L-NAME (10 μM) did not significantly alter F2-VPPE-induced vasorelaxation. Seven compounds were identified using GC-MS, including spathulenol. Conclusion: F2-VPPE exerted its endothelium-independent vasorelaxation by inhibition of vascular smooth muscle contraction induced by extracellular Ca+2 influx through trans-membrane Ca+2 channels and/or Ca+2 release from intracellular stores, and by activation of KATP channels. The vasorelaxation effects of V. pubescens could be mediated by the compound, spathulenol.